212k views
18 votes
Solve the following equations using substitution.

2x - 3y = 6
2x - y = 7

Check your answer using LS and RS method.

1 Answer

6 votes

Answer:

x = 3.75

y= 0.5

Explanation:

2x and 3y and 6

2x and y and 7

the difference between those two is 2y and 1

because 3y-y = 2y and 7-6 = 1

2y=1 y = 0.5

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

2x - 3 = 6 is also 6 + 3y = 2x

3(0.5) = 1.5

6 + 1.5 = 75.5

2x = 7.5

x= 3.75

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

check:

2(3.75) = 7.5

3(0.5) = 1.5

7.5-1.5 = 6

2(3.75) = 7.5

y= (0.5)

7.5-0.5= 7

User William Keller
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.